Altered Effective Connectivity Measured by Resting-State Functional Magnetic Resonance Imaging in Posterior Parietal-Frontal-Striatum Circuit in Patients With Disorder of Consciousness - Chen, Linglong; Rao, Bo; Li, Sirui; Gao, Lei; Xie, Yu; Dai, Xuan; Fu, Kai; Peng, Xu Zhi; Xu, Haibo (Frontiers in Neuroscience, 2022)
Objective: Disorder of consciousness (DoC), as a result of severe brain injuries, is characterized by cortical and subcortical dys-connectivity. However, researches on seed-based effective connectivity (EC) might be questioned as to the heterogeneity of prior assumptions. Methods: Functional MRI data of 16 DoC patients and 16 demographically matched healthy individuals were analyzed. Seed-based d Mapping Permutation of Subject Images (SDM-PSI) was performed to quantitatively synthesize results from neuroimaging studies that evaluated resting-state functional activity in DoC patients. Spectral dynamic causal modeling (spDCM) was used to assess how EC altered between the regions resulting in DoC patients compared to healthy individuals. Results: We found increased activity in left striatum (L stria) and decreased activity in bilateral precuneus/posterior cingulate cortex (PCC), bilateral midcingulate cortex and left middle frontal gyrus. The resulting pattern of interaction in DoC identified the disrupted connection and disturbance of posteriorparietal-frontal-striatum, and reduced self-inhibition of preCUN/PCC. The strength of self-inhibition of preCUN/PCC is negatively correlated with the total score of CRS-R. Conclusion: This impaired EC of DoC might be principally underlying the posteriorparietal-frontal-striatum circuit, especially the disruption of the mechanisms underlying damage of corticostriatal connection and possible loss of preCUN/PCC’s function as the main regulatory hub.